Sustaining knowledge management development of the ulū al-albāb approach - Mhd. Sarif, Suhaimi; Ismail, Yusof (Zes Rokman Resources, 2019)
Knowledge management development enables organizational learning to sustain competitive advantage and performance in the competitive world. There have been many ways to sustain knowledge management development. This paper postulates contingency approach of knowledge management development through the Ulū al-Albāb approach as a mean to achieve organizational sustainable innovation and competitive advantage. The knowledge-based view offers an integrative framework to achieve sustainable knowledge management and organizational learning that are driven by knowledge-based view of firm innovation. The KBV view lacks of spirituality foundation to sustain intellectual contribution from knowledge workers. An opinion survey with knowledge workers who are familiar with conventional knowledge management perceived that the Ulū al-Albāb approach is commendable insights into dynamism, uncertainty and complex business contexts. The current stage of the Ulū alAlbāb approach has to be operationalized to fit into the contemporary business models and processes. However, the views of the knowledge workers are not comprehensive and rigorous without the views from other stakeholders. Nevertheless, managers can apply the Ulū al-Albāb approach into its communities of practice and social network. The Ulū al-Albāb approach contributes to the theoretical and practical understanding of knowledge management development.